2013
DOI: 10.1002/maco.201307161
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion resistance of investment casting samples of CF8 stainless steel in different passivation conditions

Abstract: This study evaluated the corrosion performance of specimens of investment casting CF8 stainless steel, in different passivation conditions. The samples of a metallurgical industry were heat treated, blasted with steel grit, and surface treated with an aqueous solution used in the passivation process, containing 22% nitric acid and 4% hydrofluoric acid in two different situations: immediately after reset (new solution) and after use (depleted solution). Also used was a solution with a proposed passivation conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…The corrosion behavior has already been investigated for the AISI 410 SS, [5,9,[12][13][14][15] and for the 17-4 PH SS. [6,7,10,[16][17][18][19] Although some studies have demonstrated that the chemical passvation promoted an improvement on pitting corrosion resistance for other types of stainless steels, [20][21][22][23][24][25][26][27] it was not found studies relating this surface treatment to corrosion behavior of the AISI 410 and 17-4 PH SS's.…”
mentioning
confidence: 99%
“…The corrosion behavior has already been investigated for the AISI 410 SS, [5,9,[12][13][14][15] and for the 17-4 PH SS. [6,7,10,[16][17][18][19] Although some studies have demonstrated that the chemical passvation promoted an improvement on pitting corrosion resistance for other types of stainless steels, [20][21][22][23][24][25][26][27] it was not found studies relating this surface treatment to corrosion behavior of the AISI 410 and 17-4 PH SS's.…”
mentioning
confidence: 99%